Interferons, interferon-like cytokines, and their receptors - Pestka, Sidney; Krause, Christopher D.; Walter, Mark R. (Immunological reviews, 2004)
Recombinant interferon‐α (IFN‐α) was approved by regulatory agencies in many countries in 1986. As the first biotherapeutic approved, IFN‐α paved the way for the development of many other cytokines and growth factors. Nevertheless, understanding the functions of the multitude of human IFNs and IFN‐like cytokines has just touched the surface. This review summarizes the history of the purification of human IFNs and the key aspects of our current state of knowledge of human IFN genes, proteins, and receptors. All the known IFNs and IFN‐like cytokines are described [IFN‐α, IFN‐β, IFN‐ε, IFN‐κ, IFN‐ω, IFN‐δ, IFN‐τ, IFN‐γ, limitin, interleukin‐28A (IL‐28A), IL‐28B, and IL‐29] as well as their receptors and signal transduction pathways. The biological activities and clinical applications of the proteins are discussed. An extensive section on the evolution of these molecules provides some new insights into the development of these proteins as major elements of innate immunity. The overall structure of the IFNs is put into perspective in relation to their receptors and functions.